Prevalence and Management of Ocular Trauma in Two Municipalities of Nepal - Shrestha, Mohan Krishna; Basnet, Pushpa Babu; Poudel, Manish; Sharma, Shaifali; Gurung, Reeta (Nepalese Journal of Ophthalmology, 2026)
Introduction: Female Community Health Volunteers (FCHVs) play a crucial role in promoting and preventing of eye health problems. Objective: To assess the prevalence of and management of corneal abrasions using ophthalmic antimicrobials by FCHVs in urban areas of Nepal. Methodology: This retrospective study reviews the data of ocular trauma between 2019 January and 2022 December of Nilkantha and Solududhkunda Municipalities, Nepal. The FCHVs were trained to diagnose corneal abrasions and provide a 3-day course of antimicrobials and referred unresolved cases to Eye Centres for further management. Data were analysed with IBM SPSS v.20. Chi-square and Fisher’s exact tests were used. A 95% confidence interval was calculated, and significant variables were analysed through multiple logistic regression. Result: All together 1,949 ocular trauma cases utilised the community-based eye care services provided by FCHVs. The prevalence of corneal abrasion was 87.3% (1,701), with a higher prevalence in Nilkantha (70.3%; n=1,195) than Solududhkunda (29.7%; n=506). In corneal abrasion cases, the mean age ± SD of the participants were 38.9 ± 18.1, (39.4±18.2 in Nilkantha and 37.7±17.8 in Solududhkunda municipalities). The prevalence of corneal abrasion was 47.9 % (814) in male and 52.1% (887) in female. The recovery rate of corneal abrasion was 97.4% (95% CI: 96.6–98.1; p<0.001), with consistent efficacy across location, gender, and age, but significant differences by injury type and time to FCHV visit. Patients treated within 12 to 24 hours had significantly higher odds of recovery at 15.1 (95% CI: 7.2–31.7) and 12.7 (95% CI: 5.2–30.8) compared to those treated after 24 hours. Conclusion: The involvement of FCHVs in managing corneal abrasions proved effective in urban areas. Chloramphenicol Aplicap (1%) was found to be highly effective in treating corneal abrasions within 24 hours of ocular injury contributing to a reduction in corneal blindness in urban areas of Nepal.